Foundry sand recycling in the troughs of blast furnaces: a technical note - Andrade, R. M.; Cava, S.; Silva, S. N.; Soledade, LEB; Rossi, C. C.; RobertoLeite, E.; Paskocimas, C. A.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2005)
The foundry sand agglomerated with alkaline phenolic resin, used for the manufacture of molds, was found to be a residue which is able to be recycled, minimizing the costs of disposal and the environmental impact. This paper analyzes the thermomechanical regeneration and leaching processes and also assesses the influence of additives on the improvement of the mechanical properties of the sands. Besides, the industrial experiments carried out at CSN aiming at the foundry sand recycling in the covering of the blast furnace troughs are presented. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: recycling; reclamation and foundry sand